International phase I study protocol to develop a patient-reported outcome measure for adolescents and adults receiving gender-affirming treatments (the GENDER-Q) - Anne F. Klassen; Manraj Kaur; Natasha Johnson; Baudewijntje P.C. Kreukels; Giancarlo McEvenue; Shane D. Morrison; Margriet G. Mullender; Lotte Poulsen; Müjde Özer; Will Rowe; Thomas Satterwhite; Kinusan Savard; et al. (2018)
A critical barrier to outcome assessment in gender-affirming healthcare is the lack of a specific patient-reported outcome measure (PROM). This phase I protocol describes an international collaboration between investigators in Canada, Denmark, the Netherlands and the USA who have coalesced to develop a new PROM (ie, the GENDER-Q) to evaluate outcomes of psychological, hormonal and surgical gender-affirming treatments. This phase I study uses an interpretive description approach. Participants aged 16 years and older seeking any form of gender-affirming treatments in centres located in Canada, Denmark, the Netherlands and the USA will be invited to take part in qualitative interviews. Participants will review BREAST-Q and FACE-Q scales hypothesised to contain content relevant to specific gender-affirming treatments. Interviews will elicit new concepts for additional scale development. Each interview will be digitally recorded, transcribed and coded. The main outcome of this phase I study will be the development of a conceptual framework and set of scales to measure outcomes important to evaluating gender-affirming treatments. To this end, analysis will be used to add/drop/revise items of existing scales to achieve content validity. For new concepts, coding will assign top-level domains and themes/subthemes to participant quotes. Codes will be used to develop an item pool to inform scale development. Draft scales will be shown to transgender and gender diverse persons and experts to obtain feedback that will be used to refine and finalise the scales. The field-test version of the GENDER-Q will be translated by following rigorous methods to prepare for the international field-test study. This study is coordinated at McMaster University (Canada). Ethics board approval was received from the Hamilton Integrated Ethics Board (Canada), the Medical Ethical Committee at VUmc (The Netherlands) and Advarra (USA). Findings will be published in peer-reviewed journals and presented at national and international conferences and meetings.